13-Hydroxy-4,16-dimethyl-4,16-diazapentacyclo[12.3.1.01,5.05,13.07,12]octadeca-7(12),8,10-triene-6,18-dione - K. Gurunathan; J. Suresh; P. L. Nilantha Lakshman; S. Perumal; R. Suresh Kumar (Acta Crystallographica Section E, 2009)
In the title compound, C18H20N2O3, the N-methylpiperidone ring adopts a chair conformation. The pyrrolidine ring and the five-membered cyclopentane rings adopt envelope conformations. The five-membered ring of the ninhydrin system adopts an envelope conformation with the central C atom deviating by 0.217 (1)Å from the mean plane through the other atoms. The molecular packing is characterized by intermolecular C—H...O and intramolecular C—H...O and O—H...N interactions.